Features of Damage to the Organ of Vision in Coronavirus Infection - M. I. Razumovsky; A. M. Razumovskaya; Yu. A. Korovyansky (Oftalʹmologiâ, 2023)
Introduction. Recently, there have been a number of reports of damage to the posterior segment of the eyeball (retina and vascular tract) as a complication of coronavirus infection. Moreover, such lesions occur in the long term (after a few weeks or more). We also observed similar changes, sometimes with the development of a second wave of the disease. At the same time, early diagnosis of damage to the microcirculatory bed and phenomena — precursors of thrombosis (blood clotting disorders) is very important.The aim of the study was to determine the types of complications of coronovirus infection on the part of the organ of vision and their clinical form. Creation of methods for early diagnosis of the progression of possible thrombogenic processes in the anterior and posterior segments of the eyeball.Methods. The object of the study were patients with various types of complications due to coronavirus infection. The state of the bulbar microcirculation and the diagnosis of thrombotic symptoms caused by complications of coronavirus infection (COVID-19) were studied.Results. The types of complications of coronovirus infection on the part of the organ of vision and their clinical forms were determined. Methods for early diagnosis of the progression of possible thrombogenic processes in the anterior and posterior segments of the eyeball have been developed.Conclusion. As a result of a survey of 75 patients who had a coronavirus infection, it was revealed that the most common eye complications are anterior and posterior blepharitis, in addition, in some cases, damage to the microcirculatory bed of the bulbar conjunctiva was found in the form of arteriolar and venular angiitis and damage to the vessels of the posterior segment of the eyeball.